Cyber-Attack Issues: Laws & Policies and the Role of Librarians - Ghimire, Kedar (Access: An International Journal of Nepal Library Association, 2023)
Cyber security is the practice of deploying people, policies, processes and technologies to protect organizations, their critical systems and sensitive information from digital attacks. Organizations have become far more vulnerable to cyber threats because digital information and technology are now so heavily integrated into day-to-day work. But the attacks themselves, which target both information and critical infrastructure, are also becoming far more sophisticated. In this scenario, this paper especially tries to trace out major attribute of cyber-attack, common cyber-attacks that are usually seen in Nepal and periphery, laws and policies related to cyber security in Nepal, how we can make the academic environment cyber safe. To cover these issues the study reviews the academic literature dealt with cyber security, cyber security policy, and role of libraries and librarian on the cyber security. Most of the research data are the primary sources of information i.e. articles of the research journals which have been published in the last few years either in hard copy or electronically. Qualitative research method has been applied for the study.